Criticism and Self-criticism: participatory evaluation in rural schools - Ilma Ferreira Machado (Universidade Estadual Paulista Júlio de Mesquita Filho, 2010)
This paper approaches some possibilities implementation of participatory evaluation,which is seen as an important dimension of the accomplished pedagogical work inrural schools organized according to politician-pedagogical principles of the movementof landless rural workers. Among the authors who base this study are Freitas (1995),Perrenoud (1986) and Pistrak (2002). The research of participant nature, whose maininstrument was the comment had with central objective to analyze where measuredcritical and the self-criticism as a proposition of participatory evaluation, reflected in thedaily life of rural schools. The results of the research show the value of systematicevaluation in the context of these schools. It was possible to see that a transformativeand emancipatory education can not do without the critical and participatory evaluation,which includes students and educators as subjects of the process of teaching andlearning. Although it is a practice complex and sometimes conflicting, participatoryevalution is essential tool for collective reflection and systematization of educationalactivities and actions triggered in school, so as to strengthen the educational project ofthe rural social movements